Isolation of Brucella inopinata from a White’s tree frog (Litoria caerulea): pose exotic frogs a potential risk to human health? - Scholz, Holger C.; Heckers, Kim O.; Appelt, Sandra; Geier-Dömling, Dorothee; Schlegel, Patrick; Wattam, Alice R. (Frontiers in Microbiology, 2023)
Cold-blooded hosts, particularly exotic frogs, have become a newly recognized reservoir for atypical Brucella species and strains worldwide, but their pathogenicity to humans remains largely unknown. Here we report the isolation of a B. inopinata strain (FO700662) from a diseased White's Tree Frog (Litoria caerulea) in Switzerland. Originally identified as Ochrobactrum based on its rapid growth and biochemical profile, strain FO700622 was positive for the Brucella-specific markers bcsp31 and IS711. It showed the specific banding pattern of B. inopinata in conventional Bruce-ladder multiplex PCR and also had identical 16S rRNA and recA gene sequences as B. inopinata. Subsequent genome sequencing followed by core genome-based MLST (cgMLST) analysis using 2704 targets (74% of the total chromosome) revealed only 173 allelic differences compared to the type strain of B. inopinata BO1T, while previously considered the closest related strain BO2 differed in 2046 alleles. The overall average nucleotide identity (ANI) between the type strain BO1T and FO700622 was 99,89%, confirming that both strains were almost identical. In silico MLST-21 and MLVA-16 also identified strain FO700662 as B. inopinata. The nucleotide and amino acid-based phylogenetic reconstruction and subsequent comparative genome analysis again placed the isolate together with B. inopinata with 100% support. In conclusion, our data unequivocally classified strain FO700622, isolated from an exotic frog, as belonging to B. inopinata. The isolation of B. inopinata from a frog along with other reports of human infection by atypical Brucella raises the question of whether atypical Brucella could pose a risk to human health and deserves further attention.